2016
DOI: 10.1177/1091581816652605
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of Artemether–Clindamycin Nanostructured Lipid Carriers in Rats

Abstract: Currently, artemisinin-based combination therapy is considered the best option in the treatment of malaria. However, toxicity of artemisinins limits their use in pregnancy. In the absence of sufficient toxicity data, the World Health Organization recommends that artemisinins are not to be used in the first trimester of pregnancy and can be used only in second and third trimesters, when other treatments are not available. We have recently observed that drugs loaded in nanolipid carriers are selectively taken up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies of DHA (Longo, Zanoncelli, Manera, et al, 2006) and other studies of artemisinins in rats (Abolaji et al, 2013; Adebisi, 2008, 2010; Boareto et al, 2008, 2012, 2013; Chung, Yu, Lee, & Lee, 2013; Clark, Brannen, Sanders, & Hoberman, 2011; El‐Dakdoky, 2009; Jain, et al, 2016; Rath, Jena, Samal, & Rath, 2010), rat whole embryo culture (Longo, Zanoncelli, Manera, et al, 2006; Longo, Zanoncelli, Torre, et al, 2006), and rabbits (Schmuck, Klaus, Krotlinger, & Langewische, 2009) have shown a similar pattern of embryo death and/or cardiovascular malformations. Studies conducted since 2007 were recently reviewed by González et al, 2020.…”
Section: Artemisininsmentioning
confidence: 99%
“…Studies of DHA (Longo, Zanoncelli, Manera, et al, 2006) and other studies of artemisinins in rats (Abolaji et al, 2013; Adebisi, 2008, 2010; Boareto et al, 2008, 2012, 2013; Chung, Yu, Lee, & Lee, 2013; Clark, Brannen, Sanders, & Hoberman, 2011; El‐Dakdoky, 2009; Jain, et al, 2016; Rath, Jena, Samal, & Rath, 2010), rat whole embryo culture (Longo, Zanoncelli, Manera, et al, 2006; Longo, Zanoncelli, Torre, et al, 2006), and rabbits (Schmuck, Klaus, Krotlinger, & Langewische, 2009) have shown a similar pattern of embryo death and/or cardiovascular malformations. Studies conducted since 2007 were recently reviewed by González et al, 2020.…”
Section: Artemisininsmentioning
confidence: 99%
“…Nevertheless, should this nanoparticle formulation be further developed as drug, its use in pregnancy must be excluded. 167…”
Section: Embryotoxicity and Teratogenicitymentioning
confidence: 99%